TINGKAT KEPATUHAN WAJIB PAJAK DI MASA NEW NORMAL PADA UMKM DI KOTA PONTIANAK - Sari, Wilda; Kristiawati, Endang; Wulandari, Renny (Jurnal Akuntansi, Auditing dan Investasi, 2021)
This study aims to determine the level of taxpayer compliance in payingtaxes in the new normal period and economic recovery for UMKMactors in the city of Pontianak. The population in this study were UMKMactors in Pontianak City, while the sample in this study were UMKMactors in every sub-district of Pontianak City which were classified asmicro and small business actors. The research method uses a qualitativeapproach. The results of this study indicate that taxpayers who stillsurvive in the economy in the new normal period still have a level ofcompliance in taxation by considering the many policies provided by thegovernment for UMKM actors so that it does not affect their obligationsin taxation. Keywords: Taxpayer compliance, the new normal period, UMKM